2009
DOI: 10.1007/s00125-009-1516-3
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption and risk of type 2 diabetes

Abstract: Aims/hypothesis The aim of this study was to examine the association of consumption of coffee and tea, separately and in total, with risk of type 2 diabetes and which factors mediate these relations. Methods This research was conducted as part of the Dutch Contribution to the European Prospective Investigation into Cancer and Nutrition, which involves a prospective cohort of 40,011 participants with a mean follow-up of 10 years. A validated food-frequency questionnaire was used to assess coffee and tea consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 41 publications
4
82
0
5
Order By: Relevance
“…For instance, in a population‐based cohort of ~40 000 Dutch individuals, higher tea consumption (ranging from 0 to 1 cups per day to > 5 cups per day) was associated not only with a lower prevalence of current smoking, but also with a reduction in alcohol consumption, body mass index (BMI) and total energy intake. In contrast, higher coffee consumption was accompanied by a higher prevalence of current smoking and higher alcohol consumption, BMI and total energy intake 15. High correlations between smoking, alcohol and cannabis have been reported previously 16, 17, 18.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, in a population‐based cohort of ~40 000 Dutch individuals, higher tea consumption (ranging from 0 to 1 cups per day to > 5 cups per day) was associated not only with a lower prevalence of current smoking, but also with a reduction in alcohol consumption, body mass index (BMI) and total energy intake. In contrast, higher coffee consumption was accompanied by a higher prevalence of current smoking and higher alcohol consumption, BMI and total energy intake 15. High correlations between smoking, alcohol and cannabis have been reported previously 16, 17, 18.…”
Section: Discussionmentioning
confidence: 56%
“…Because tea is the most widely consumed beverage worldwide (Higdon and Frei, 2003), and because numerous epidemiological studies have suggested tea may have a role in reducing risk of diabetes (Greenberg et al, 2005;Song et al, 2005;Iso et al, 2006;Odegaard et al, 2008;Polychronopoulos et al, 2008;Jing et al, 2009;van Dieren et al, 2009), controlled intervention studies are important for defining the potential for tea to maintain healthy glucose metabolism. Oolong tea processing involves fermenting the product more than green tea is fermented, but less than black tea.…”
Section: Discussionmentioning
confidence: 99%
“…From the National Health and Nutrition Examination Survey (NHANES) follow-up Study, there was an inverse relationship between tea intake in general and diabetes risk, but only for adults under 60 years of age who had recently lost weight (Greenberg et al, 2005). Results from a food frequency questionnaire distributed to 40 011 participants of the European Prospective Investigation into Cancer and Nutrition suggested that tea consumption was inversely associated with type 2 diabetes (van Dieren et al, 2009). A small study of 542 men and women from Cyprus, Mitilini and Samothraki islands showed that tea intake was associated with lower glucose levels in non-obese (Polychronopoulos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dabei verringerte jede Tasse Kaffee pro Tag das Diabetesrisiko um 7% [36]. Dieser Zusammenhang war durch Adjustierung auf einzelne Inhaltsstoffe nicht erklärbar [37]. Die Auswertungen weiterer Langzeitbeobachtungen [38][39][40][41][42] und Querschnittsanalysen [43] ergaben übereinstimmend ein geringeres Auftreten von beeinträchtigter Glukosetoleranz und Typ-2-Diabetes mit steigendem Kaffeekonsum.…”
Section: Kaffee Und Der Schutz Vor Typ-2-diabetesunclassified